Dreaming beyond home: Factors shaping Bangladeshi women's aspirations for overseas higher education - Nishat Tabassum; Faria Mubashira (An-Nisa’ Journal of Gender Studies, 2026)
The increasing number of Bangladeshi female students pursuing higher education abroad reflects domestic challenges, including limited educational quality, restricted employment opportunities, and socio-political conditions that encourage international academic migration. This study aims to analyze the factors influencing Bangladeshi female students’ decisions to pursue higher education abroad and to examine the socio-cultural influences shaping their aspirations for international study. The study employed a quantitative approach using a cross-sectional survey design involving 200 Bangladeshi female students through questionnaires, convenience sampling, and descriptive SPSS analysis to identify motivations and the influence of socio-cultural norms. The findings reveal two key points. First, Bangladeshi female students are motivated to study abroad by push factors, including political instability, low educational quality, and limited research opportunities, alongside pull factors such as international reputation, self-development, independence, and family support. Second, cultural and social norms influence aspirations differently: Pabna University of Science and Technology students receive stronger support, while University of Dhaka students face greater family resistance despite pursuing independence and global education. This study concludes that Bangladeshi female students perceive overseas education as a strategy to overcome domestic limitations, achieve social mobility, and attain independence through the interaction of push factors, pull factors, and family cultural support. The study contributes to educational policy by emphasizing the strengthening of university roles, family support, and government collaboration in expanding access and motivation for female students to pursue international higher education.